Emergency mesenteric embolectomy - Matteucci, Pablo; Bouton, Jorge; Canessa, Germán (Cirugía del Uruguay, 1974)
A patient convalescing from the second miocardial infarction developed abdominal pains and was operated upon. The cause was found to be obstruction of superior mesenteric artery and embolectomy was performed in order to restablish circulation. The patient recovered completely.